Congenital absence of the right carotid artery with a left carotid artery pseudoaneurysm: a case report - Chen, Miaomiao; Tang, Junxiang; Iqbal, Muhammad Asad (Frontiers in Surgery, 2025)
A unilateral carotid artery pseudoaneurysm combined with a congenital absence of the contralateral internal carotid artery is clinically rare, and the currently available literature is limited. This article reports a case of a 37-year-old male patient with a left carotid artery pseudoaneurysm and congenital absence of the right common and internal carotid arteries, initially presenting with a neck mass. The patient recovered well 2 years after surgery.